Cooperative and fresher encounter algorithm for reducing delay in MANET - Noor Alleema; D. Siva Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In Mobile Ad-hoc Networks (MANET), the route discovery is the chief problem for the nodes. In this paper Cooperative and Fresher Encounter Algorithm (CFEA) for Reducing Delay in MANET is proposed. The route discovery problem has been overcome by FResher Encounter algorithm. It is a simple algorithm for discovery the routes in efficient manner in the MANET. The node has the memory of past route details that communicate with remaining nodes. The node prefers to find the intermediate node instead of finding the destination node, that intermediate node keeps the knowledge of recently encounter the destination node. Then the intermediate node communicates with the node which is encountered the destination node recently, and the process is continued until the destination is attained. The main advantage of the scheme is reducing the process time.